Drumming in Bhaktapur Music of the Newar People of Nepal. Volume I: Text - Wegner, Gert-Matthias (Documenta Nepalica: Book Series, 2023)
This groundbreaking publication offers a unique resource of information about one of the most glorious and diverse musical cultures of the Himalayas. The numerous drum traditions of Bhaktapur in the Kathmandu Valley are a vibrant aspect of traditional Newar culture that saw its heyday between the thirteenth and eighteenth centuries. The three Malla kingdoms of Bhaktapur, Lalitpur and Kathmandu competed in art, architecture, music, dance and opulent town rituals celebrating the presence of the gods. Music served as a portal between the human world and the realm of the gods. This study documents the role and repertoires of the different percussion genres in a transcribed and commented form for practical use and as a teaching aid. It also includes a dictionary of Newari terms related to music. As it focuses on the musical life of Bhaktapur during the decade starting from 1983, it could serve as a point of reference for comparison with the present situation. This publication is an outstanding contribution to the preservation of Newar culture.